Promoting Healthy Lifestyle Strategies among Couples for Sustainable Family Survival in Oyo State, Nigeria - Taiwo Adekemi Akinyemi; Olajide Olatunde Adeola; Halimot Omobola Toriola (International Journal of Home Economics, Hospitality and Allied Research)
The study examines healthy lifestyle strategies among 1,086,543 couples in Oyo State, Nigeria, focusing on feeding, physical well-being, and mental health. Data from 817 married respondents revealed that 73.6% prefer self-prepared meals, while 9.5% prefer fast food or processed food. Consumption of vegetables and fruits varied, with 55.4% following a balanced diet. The study reveals that people living in clean environments are generally satisfied with their living conditions, with a high percentage of those living in spacious, secure homes. Couples living in houses with cross ventilation are also satisfied. Physical exercise is also a significant factor. The study shows that 59.9% of respondents practice mindfulness and meditation, while 34.8% seek mental health advice. 21.7% are aware of local mental support services. Balancing work-life is a challenge, with 33.9% excelling and 37.3% good. Strong preferences for self-prepared meals and regular physical exercise support mental health. Healthy lifestyle can be encouraged through mindfulness, with secure communities and local mental support resources playing a key role. The results of the study will pave the way for new fields of research by providing material for health educators and educational researchers, as well as guidance on healthy lifestyles for individuals, couples, families, the government, and non-governmental organizations.